Hemophagocytic Lymphohistiocytosis in the Emergency Department: Recognizing and Evaluating a Hidden Threat - Morrissette, Katelin (J Emerg Med, 2021)
BACKGROUND: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hematologic disorder resulting from an ineffective and pathologic activation of the immune response system that may mimic common emergency department presentations, including sepsis, acute liver failure, disseminated intravascular coagulation, and flu-like illnesses such as coronavirus disease 2019 (COVID-19). OBJECTIVE: This narrative review provides a summary of the disease and recommendations for the recognition and diagnostic evaluation of HLH with a focus on the emergency clinician. DISCUSSION: Though the condition is rare, mortality rates are high, ranging from 20% to 80% and increasing with delays in treatment. Importantly, HLH has been recognized as a severe variation of the cytokine storm associated with COVID-19. Common features include a history of infection or malignancy, fever, splenomegaly or hepatomegaly, hyperferritinemia, cytopenias, coagulopathies, abnormal liver enzymes, and hypertriglyceridemia. Using specific features of the history, physical examination, laboratory studies, and tools such as the HScore, HLH-2004/2009, and hyperferritinemia thresholds, the emergency clinician can risk-stratify patients and admit for definitive testing. Once diagnosed, disease specific treatment can be initiated. CONCLUSION: This review describes the relevant pathophysiology, common presentation findings, and a framework for risk stratification in the emergency department.